Social-ecological transformation of former illegal gold miners through the Cisangku conservation village model - Nur Azisyah Mukmin; Yudianto; Sultrayansa (CV. Literasi Indonesia, 2026)
Illegal Gold Mining (IGM) represents a complex social-ecological issue that contributes to environmental degradation, social vulnerability, and unsustainable community livelihoods. This study aims to analyze the process of social-ecological transformation among former illegal gold miners through the Cisangku Conservation Village Model (CVM) in the buffer zone of Gunung Halimun Salak National Park. A qualitative approach with a descriptive research design was employed. Data were collected through in-depth interviews, field observations, and document analysis. Data analysis involved data reduction, data presentation, and conclusion drawing, with validity ensured through source, method, and time triangulation. The findings indicate that the Cisangku Conservation Village Model has facilitated social-ecological transformation by shifting community livelihoods from illegal gold mining to conservation-based economic activities, including traditional ground coffee production, endemic plant seedling nurseries, and conservation-based ecotourism. These livelihood transitions increased the average income of members by 42%, expanded employment opportunities for vulnerable groups, engaged 69% of former illegal miners in conservation activities, and supported environmental rehabilitation through the planting of 356,000 trees. The transformation process was driven by collaboration among government agencies, the private sector, local communities, and the leadership of a local hero, which strengthened community participation and promoted behavioral change. The study concludes that conservation-based community empowerment is an effective strategy for achieving social-ecological transformation, strengthening sustainable livelihoods, and supporting sustainable development.